Wordwall on Mastery of Vocabulary in English Learning - Syamsidar Syamsidar; Ronald Maraden Parlindungan Silalahi; Ana Rusmardiana; Fida Febriningsih; Mujahid Taha; Erniwati Erniwati (STAI Hubbulwathan Duri, 2023)
This study aims to analyze the effectiveness of wordwalls on vocabulary mastery in learning English. The research method used is quantitative with a one-shot case study, namely grade 8 junior high school. Data was collected through a questionnaire with a Likert Scale. Data analysis techniques use techniques to determine effectiveness and percentages. This study concluded that on the pronunciation indicator, as many as ten students stated that they strongly agreed, and only 1 student stated that they did not agree with a percentage of 74.3%. Furthermore, in the spelling indicator, as many as seven students stated that they strongly agreed, and 2 students stated that they did not agree with a percentage of 72.1%. Furthermore, the indicator of meaning, as many as 8 students stated that they strongly agreed and 2 students stated that they did not agree with a percentage of 74.3%. Thus, an effective wordwall improves vocabulary mastery by 73.5% or is effective in learning English.